Identification of Key Genes Associated With Early Calf-Hood Nutrition in Subcutaneous and Visceral Adipose Tissues by Co-Expression Analysis - Pan, Cuili; Yang, Chaoyun; Ma, Yanfen; Sheng, Hui; Lei, Zhaoxiong; Wang, Shuzhe; Hu, Honghong; Feng, Xue; Zhang, Junxing; Ma, Yun (Frontiers in Veterinary Science, 2022)
Background Substantive evidence has confirmed that nutrition state is associated with health risk and the onset of pubertal and metabolic profile. Due to heterogeneity, adipose tissues in different anatomical positions tend to show various metabolic mechanisms for nutrition. To date, the complicated molecular mechanisms of early calf-hood nutrition on bovine adipose tissue are still largely unknown. This study aimed to identify key genes and functionally enriched pathways associated with early calf-hood nutrition in visceral and subcutaneous adipose tissue. Results The RNA-seq data of visceral and subcutaneous adipose tissues of calves feeding on low and high dietary nutrition for more than 100 days were downloaded and analyzed by weighted gene co-expression network analysis (WGCNA). Two modules that positively associated with a low plane of nutrition diet and two modules with a high plane of nutrition diet were identified in the subcutaneous adipose tissue. The blue and yellow modules, most closely associated with low and high nutrition, were selected for the functional enrichment analysis and exploration of hub genes. The results showed that genes in the blue module were significantly enriched in pathways that related to fat metabolism, reproduction, and cell communication. Genes in the yellow module were enriched in pathways related to fat metabolism, reproduction, cell proliferation, and senescence. Meanwhile, the blue and brown modules in visceral adipose tissue were most closely associated with low and high nutrition, respectively. Notably, genes of the blue module were significantly enriched in pathways related to substance metabolism, and genes in the brown module were significantly enriched in energy metabolism and disease pathways. Finally, key genes in subcutaneous adipose tissue for low nutrition (PLCG1, GNA11, and ANXA5) and high nutrition (BUB1B, ASPM, RRM2, PBK, NCAPG, and MKI67), and visceral adipose tissue for low nutrition (RPS5, RPL4, RPL14, and RPLP0) and high nutrition (SDHA and AKT1) were obtained and verified. Conclusion The study applied WGCNA to identify hub genes and functionally enriched pathways in subcutaneous and visceral adipose tissue and provided a basis for studying the effect of early calf-hood nutrition on the two adipose tissue types.